2022
DOI: 10.3390/cancers14041026
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Molecular Markers in Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is the second most common primary liver cancer and subsumes a heterogeneous group of malignant tumors arising from the intra- or extrahepatic biliary tract epithelium. A rising mortality from CCA has been reported worldwide during the last decade, despite significant improvement of surgical and palliative treatment. Over 50% of CCAs originate from proximal extrahepatic bile ducts and constitute the most common CCA entity in the Western world. Clinicopathological characteristics such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 196 publications
(209 reference statements)
1
16
0
2
Order By: Relevance
“…A total of 98.64% patients developed any-grade AEs and 52.70% developed grade 3/4 AEs. The results were similar to those of recent studies involving a single agent and combined regimens treating refractory advanced BTCs ( 7 , 15 , 18 21 ). This combination regimen prolonged the survival duration in both second- and above-line systemic therapies, without significant difference ( p = 0.809).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A total of 98.64% patients developed any-grade AEs and 52.70% developed grade 3/4 AEs. The results were similar to those of recent studies involving a single agent and combined regimens treating refractory advanced BTCs ( 7 , 15 , 18 21 ). This combination regimen prolonged the survival duration in both second- and above-line systemic therapies, without significant difference ( p = 0.809).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, this study found that 56.75% of the population got a worse ECOG physical score, which partly played a negative role in ensuring patients' compliance. The long-term survival of patients with BTCs was dismal, with 5-year survival rates of 10%-50% (1,21). ABC-01 and ABC-02 clinical trials established the standard of CisGem as a first-line systemic therapy in local advanced and metastatic BTCs (2,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, next‐generation sequencing revealed molecular subtypes of iCCA that carry prognostic and predictive potential, 27 while the pathological criteria of lymph node and lymphovascular invasion are well‐characterized prognostic factors across European and Asian patient collectives 26,28 . At the same time, patient‐ or host‐centred determinants of prognosis remain relatively unexplored in this rare tumour entity 29 . Accordingly, we investigated tumour aetiology together with body composition in a large, homogenous European cohort of patients undergoing curative‐intent liver resection for iCCA.…”
Section: Discussionmentioning
confidence: 99%
“… 44 During gemcitabine chemotherapy, a reduction in CA19-9 equal to or more than 50% correlated with improved therapy response and increased survival but its sensitivity and specificity is 72% and 84%, respectively. 45 Changes in serum CA 19-9 could therefore be used to identify high-risk patients and therefore those who are more likely to benefit from adjuvant therapy. 44 Rather than absolute levels, an observed change may be more applicable but approximately 10% of the general population are Lewis blood group antigen negative and unable to produce CA 19-9.…”
Section: Patient Stratification and Biomarkers For Adjuvant Chemotherapymentioning
confidence: 99%